Object Oriented Programming, Learning OOP Concepts (Class, Object, Inheritance, Polymorphism), Benefits and Application Methods (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
When we learn programming, we will definitely come to the concept of object oriented programming (OOP). For many people, this stage seems a bit incomprehensible and complicated. Actually it is not.To understand OOP, let's first look at classical programming. The point is that the first computers and programs were aimed at solving mathematical problems. Such programs received some data from the user, performed various arithmetic operations following a strict sequence, and returned the user's expected result at the end of the program. That is why such programs are called linear or sequential programs.